Vocabulary and Language Skills Development in Early Childhood Through Storytelling and Role-Playing Methods in Rainbows Kindergarten - Amali, Sakhia; Sudirman, Aprillah (Journal of Early Childhood Education (JECE), 2024)
In developing children's storytelling abilities, teachers and parents must provide stimulation in guiding children's speaking by introducing lots of vocabulary so that children can tell stories well without misunderstandings. Language acquisition in early childhood begins through hearing what they hear around them, which is called receptive language. Storytelling is a language learning method in schools for developing children's language. Learning storytelling allows students to express experiences, describe objects, explain intent/meaning, and creative imagination. School is a means for children where the process of children's language development is shed through sociality. It is stated that 50% of Kindergarten A children at Rainbows Kindergarten already speak well and correctly, while Playgroup is in the interactive stage of developing their language. The storytelling method in kindergarten uses a second language and the Indonesian language.